Processing Challenges and Strategies for a Robust Ultrathin Solid Electrolyte Membrane in Sulfide-Based All-Solid-State Batteries - Kim, Subin; Shin, Chaeyeon; Cho, Jinhan; Lee, Jieun (AMER CHEMICAL SOC, 2025)
All-solid-state batteries (ASSBs) have garnered significant attention as next-generation energy storage systems, offering high theoretical energy density and enhanced safety, and are thus considered as potential replacements for conventional liquid-based lithium-ion batteries (LIBs). Among various solid electrolytes (SEs), sulfide-based SEs are regarded as leading candidates due to their outstanding room-temperature ionic conductivity and excellent processability. Despite their advantages, the fabrication of ultrathin SE membranes remains a critical bottleneck for achieving both high energy density and cost-effective production in practical ASSB systems. In this perspective, we present an overview of the key challenges associated with ultrathin sulfide-based SE membranes, along with design criteria and recent strategies to address these issues. Particular emphasis is placed on state-of-the-art fabrication techniques, including solution casting, dry film processing, scaffold support, and pressurization-based densification, which enable the formation of ultrathin SE layers. Finally, we provide a perspective on future research directions toward the reliable integration of ultrathin sulfide SE membranes into large-format ASSBs.